Literatur Review : Hubungan Indeks Massa Tubuh (IMT) dengan Massa Otot pada Lansia - Dina Niswatin; Wiwit Agung Sri Nur Cahyawati; Lena Rosida (Homeostasis, 2021)
Abstract: Elderly are individuals aged 60 years and over. The nutritional status of elderly can be assessed by body mass index (BMI). BMI is related to muscle mass. BMI describes the overall body composition such as muscle, bone and fat. This paper aims to determine the relationship between BMI and muscle mass in the elderly. The writing is done by analyzing literature from medical journal database search results, namely PubMed – MEDLINE and Google Scholar. Articles included in English and published 2010-2020. A total of 20 articles are included in this literature review. BMI in the elderly is quite diverse, the elderly can have an abnormal BMI, namely underweight, overweight, and obese. The muscle mass of elderly men is greater than elderly women. The muscle mass of sarcopeni elderly has decreased compared to non-sarcopeni elderly. The relationship between BMI and muscle mass in the elderly showed mixed results, including a positive correlation between BMI and muscle mass and BMI as a risk factor and an important factor for sarcopeni. Keywords: elderly, body mass index, muscle mass, sarcopeni, bioelectrical impedance analysis Abstrak: Lansia adalah individu yang berusia 60 tahun ke atas. Status gizi lansia dapat dinilai dengan indeks massa tubuh (IMT). IMT berhubungan dengan massa otot. IMT menggambarkan komposisi tubuh secara keseluruhan seperti otot, tulang, dan lemak. Tulisan ini bertujuan untuk mengetahui hubungan IMT dengan massa otot pada lansia.  Penulisan dilakukan dengan menganalisis literatur dari hasil pencarian database jurnal kedokteran, yaitu PubMed–MEDLINE dan Google Scholar. Artikel yang disertakan menggunakan bahasa Inggris dan dipublikasikan tahun 2010-2020. Sebanyak 20 artikel disertakan pada literature review ini. IMT pada lansia cukup beragam, lansia dapat memiliki IMT abnormal yaitu underweight, overweight, dan obesitas. Massa otot lansia laki-laki rata-rata lebih besar dari lansia wanita. Massa otot lansia sarcopeni lebih rendah dari lansia non-sarcopeni. Hubungan IMT dengan massa otot pada lansia menunjukkan adanya korelasi positif IMT dengan massa otot, serta terkait IMT sebagai faktor risiko dan faktor penting terjadinya sarcopeni. Kata-kata kunci:  lansia, indeks massa tubuh, massa otot, sarcopeni,  bioelectrical impedance analysis